2014
DOI: 10.1103/physrevstper.10.020102
|View full text |Cite
|
Sign up to set email alerts
|

Applying model analysis to a resource-based analysis of the Force and Motion Conceptual Evaluation

Abstract: Previously, we analyzed the Force and Motion Conceptual Evaluation in terms of a resources-based model that allows for clustering of questions so as to provide useful information on how students correctly or incorrectly reason about physics. In this paper, we apply model analysis to show that the associated model plots provide more information regarding the results of investigations using these question clusters than normalized gain graphs. We provide examples from two different institutions to show how the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…The three distinct clusters described by Thornton et al have been studied at the item level [51,52]. In 2008, Smith and Wittmann introduced revised clusters and investigated student response patterns on those sets of items.…”
Section: Fmcementioning
confidence: 99%
See 1 more Smart Citation
“…The three distinct clusters described by Thornton et al have been studied at the item level [51,52]. In 2008, Smith and Wittmann introduced revised clusters and investigated student response patterns on those sets of items.…”
Section: Fmcementioning
confidence: 99%
“…They also introduced cluster 40_43 as velocity graphs [51]. In 2014, Smith, Wittmann, and Carter used these revised clusters to provide insight into the effectiveness of interactive classroom techniques [52].…”
Section: Fmcementioning
confidence: 99%
“…"Acceleration Graph" items (items [22][23][24][25][26] ask students to select the graph which correctly represents the acceleration of a toy car moving on a horizontal surface. "Coin Toss -Acceleration" items (items [27][28][29] ask students to select the acceleration of a coin tossed in the air. "Newton III" items (items [30][31][32][33][34][35][36][37][38][39] ask students about the forces during a variety of interactions between cars and trucks.…”
Section: A the Fmce Instrumentmentioning
confidence: 99%
“…Smith, Wittmann, and Carter found that learning trends differed on the Force Sled question cluster (in which answer choices are presented as descriptions of forces) and the Force Graphs cluster (answers as graphs of force vs. time) [2]; however, the cause of these differences is yet unknown. Do students struggle to interpret graphs of forces as is well documented for graphs of kinematic quantities [3,4]?…”
Section: Introductionmentioning
confidence: 99%
“…We are particularly interested in documenting cases in which students have a relatively high tendency to exist in a superposition or mixed-model state (selecting incoherent responses within a case) [6], and identifying possible hierarchies in student learning for various questions [7]. To highlight various aspects of our results we present examples from three different schools, two of which were previously analyzed [2]. All courses used research-validated instructional materials.…”
mentioning
confidence: 99%